Premolar Extraction Affects Mandibular Kinematics - Londoño, Alejandra; Assis, Miguel; Fornai, Cinzia; Greven, Markus (European Journal of Dentistry, 2022)
Objectives The practice of premolar extraction in orthodontics is controversial for its potential detrimental effects on the stomatognathic system. However, the ways in which premolar extraction affects mandibular function are still poorly understood. The purpose of this study was to assess the influence of premolar extraction on mandibular kinematics by evaluating axiographic tracings.Materials and Methods Forty-five orthodontically treated patients with premolar teeth extraction were compared with 45 paired untreated controls, selected for the absence of malocclusions. Systematic three-dimensional axiographic recordings of the mandibular movements were performed for protrusive–retrusive movements and speech. The transversal deviations and length of the movements were recorded for both sides along with the rotation angle during speech.Statistical Analysis Differences between the axiographic variables were analyzed via the permutation test and Wilcoxon rank-sum test. Linear regression was performed to test whether axiographic parameters were predictive of group affiliation. Dot plots were used to explore the distribution of each of the axiographic outcomes, and isometric principal component analysis to assess the differences between the cumulative effects of premolar extraction on jaw motion.Results The mandibular lateral translation in protrusion–retrusion and speech, the amount of rotation as well as the length of mandibular movements during speech were significantly higher in the treated subjects than in the controls, while retral stability did not differ. The linear regression yielded significant results for the mandibular lateral translation in protrusion–retrusion. The isometric principal component analysis showed higher values of the axiographic variables for 11 out of 45 individuals in the study sample compared with the control group.Conclusions Premolar extraction altered mandibular kinematics in at least 25% of the cases within our sample, and the transversal discrepancy between protrusive and retrusive tracings was even predictive of group affiliation. These results support the notion that the routine practice of premolar extraction as part of the orthodontic treatment should be discouraged. It is compelling to perform further studies to assess whether a disrupted kinematics of the mandible is associated to temporomandibular disorders.
Keywords: jaw tracking; axiography; premolar extraction; mandibular function; orthodontic treatment; temporomandibular disorders